Intervención de enfermería y su relación en la práctica del autoexamen de mamas en mujeres que acuden al Centro de Salud Galo Plaza Cantón Quevedo periodo octubre 2018 - abril 2019 - Domínguez Romero, Karen Andreina (2019)
The present work aims to determine the relationship that nursing intervention has in the practice of breast self-examination according to the humanistic approach, since this holistic model considers nursing care from the specialized care provided by one human to another. The variables were: nursing intervention (independent variable) and breast self-examination (dependent variable). 98 women between 20 and 50 years old attended the "Galo Plaza" Health Center, an institution located in the Quevedo canton. It corresponds to a mixed research (quantitative-qualitative), exploratory-descriptive methodology; non-experimental research, transeccional or transversal. Obtained the authorization of the director of the nursing home and the District, plus informed consent of the women, the structured interview technique was used together with its survey instrument, which was validated and approved by the Expert Judgment technique. Based on the theoretical search of representative authors and current research in the area, the results show that the nursing intervention is directly related to the promotion of women's health and prevention of diseases, in the knowledge and proper practice of breast self-examination. It was also known that the level of knowledge and practice is low due to: confusion with the gynecological consultation physical examination, ignoring the procedure, frequency and time of the menstrual cycle, and because they indicate not feeling sick, not considering it necessary and careless; all this despite knowing the importance of palpating and observing early any abnormality of the breast tissue.